Intelligente autrement : de la « Smart city » à la « Fab city ». Émergence d’un modèle alternatif de ville « intelligente » et logiques de reconfiguration du collectif urbain - Yannick Rumpala (Métropoles)
Is the "Smart City" the only "smart" city model? Not necessarily, if we consider the space opened by the "Fab City" project, which expands the model of fab labs and seems to constitute an alternative model of urban functioning. In this model, production is returned to city level, close to the inhabitants, with the promise of being able to provide some basic needs, notably through manufacturing workshops that are located in the neighborhoods and that put relatively advanced machines at the disposal of local communities. Proponents of the "Fab City" promote a city where citizens become (again) manufacturers and take possession of their own needs, reclaiming technologies collaboratively and contributing to a control of various flows (materials, energy, etc.) which condition urban ecological situations. In order to evaluate to what extent this project can constitute an "alternative urban policy", this contribution begins by studying the conditions of emergence and the logics on which it was built, so as to better identify the vision it rests on and its embedded socio-technical dimensions. The contribution then specifies the issues that are reframed and the strategic implications that result from them, demonstrating how this approach tends to displace ways of considering cities and their functioning.